O limiar de esforço percebido (LEP) corresponde à potência crítica e a um indicador de máximo estado estável de consumo de oxigěnio - Nakamura, Fábio Yuzo [UNESP]; Brunetto, Antônio Fernando; Müller Hirai, Daniel; Tesini Rosequini, Bruno; Kokubun, Eduardo [UNESP] (FapUNIFESP (SciELO), 2005)
The perceived exertion has been a target of several investigations, many times with association with objective physiological indicators in exercise. Recently, the identification of the perceived exertion threshold (PET) was proposed in the water running, which presented no difference in relation to the critical velocity. Theoretically, both parameters would be indicators of the maximum steady state of variables such as V̇O2 and blood lactate. The objective of this work was to verify the coincidence between PET, critical power (PCrit) and an indicator of maximum V̇O2 steady state (PCrit') in cycle ergometer. Eight male participants were submitted to progressive effort test in order to determine V̇O2peak (46.7 ± 8.5 ml/kg/min) and to four rectangular tests until exhaustion for the estimation of the critical power model parameters, PET and PCrit'. The hyperbolic relation between mechanical power and time spent for the V̇O2peak to be reached in each test was used for the PCrit' estimation, considered as the asymptote in the power axis, and the portion of the anaerobic work capacity (CTAnaer) depleted up to the establishment of the V̇O2peak (CTAnaer'). In order to identify PET, the straight lines angular coefficients of the perceived exertion in time (ordinate) and the powers used (abscissa) were adjusted to a linear function that provided a point in the power axis in which the perceived exertion would be kept indefinitely stable. The parameters PCrit and CTAnaer were estimated by means of the power-time non-linear equation. In order to compare the estimations of PET, PCrit and PCrit', the analysis of variance ANOVA for repeated measurements was employed, and the associations were established through the Pearson correlation. CTAnaer and CTAnaer' were compared through the t test. PET (180 W ± 61 W), PCrit (174 W ± 43 W) and PCrit' (176 W ± 48 W) were not significantly different and the correlations were of 0.92-0.98. CTAnaer' (14,080 ± 5,219 J) was lower than CTAnaer (22,093 ± 9,042 J). One concludes that the PET predicts the intensity of PCrit and PCrit' with accuracy.
The perceived exertion threshold (PET) corresponds to the critical power and to an indicator of maximal oxygen uptake steady state
Keywords: Critical power; Maximum VO2 steady state; Perceived exertion; accuracy; adult; anaerobic capacity; analysis of variance; bicycle ergometer; constants and coefficients; correlation analysis; exhaustion; human; human experiment; male; muscle exercise; muscle strength; musculoskeletal system parameters; normal human; oxygen consumption; running; self concept; steady state; time; work capacity